Effectiveness of inmates’ educational programs in Ilorin Remand Home, Nigeria - Abdulaziz Isiaka; Rasheed Shofiu Adewuyi (Intelektual Pustaka Media Utama, 2020)
Investigating the effectiveness of inmates’ educational programs was the major focused of this research in Ilorin remand homes, Nigeria. Specifically inmates’ views on effectiveness of vocational and literacy educational program were investigated. This study was descriptive survey.108 inmates were sampled using simple random sampling technique. Two research questions were formulated and a researcher’ designed questionnaires containing10 items in two sections with 4-point rating scale was used for data collection while data collected were analyzed using mean scores and standard deviation. The result showed that most inmates positively acknowledged literacy education in recreational, guidance and counseling, religious and social sciences as highly effective and effective respectively and the result also established that most inmates acknowledged vocational education in fashion designing, laundry/dry-cleaning, catering/home management, metal fabrication and electrical maintenance work as highly effective and effective respectively. It was concluded that literacy and vocational education policy for the inmates should be vigorously pursued and implemented in Ilorin, Nigeria. In addition, government and private organization should invest in inmates’ literacy and vocational education to correct the erroneous impression that under play inmates’ education which leads to their stigmatization at the point of re-entry into the society.